Institutional Multiplicity and the Fight Against Corruption: A Research Agenda for the Brazilian Accountability Network - Mariana Mota Prado; Eduardo Cornelius (Revista Direito GV)
Abstract Since democratization, Brazil has established a robust network of accountability institutions that perform a myriad of functions in combating corruption. While there is empirical research on the inner workings of the Brazilian accountability network, many questions remain unanswered and many dimensions of the interactions between institutions in this system have yet to be analyzed and uncovered. This paper argues that the accountability literature can benefit from further descriptive empirical studies, especially detailed analyses that account for empirical differences in norms, procedures and sanctions. To promote this type of granular empirical analysis, we formulate a research agenda for the Brazilian accountability system, arguing that the concept of institutional multiplicity has much to offer in this endeavour. Considering the difficulty in capturing the complexity of Brazil's vast network of accountability institutions in a single paper, we focus on the accountability systems for civil servants working for the federal executive branch. Despite being focused on a particular dimension of the accountability system, we hope that the topics proposed here can inform research questions about other areas of the system as well.